2014
DOI: 10.3390/v6041823
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated microRNA Expression in Serum of Non-Vaccinated Children with Varicella

Abstract: Circulating microRNAs (miRNAs) may play an important role in pathogen-host interactions and can serve as molecular markers for the detection of infectious diseases. To date, the relationship between circulating miRNAs and varicella-zoster virus (VZV) caused varicella has not been reported. Using TaqMan Low-Density Array (TLDA) analysis, expression levels of miRNAs in serum samples from 29 patients with varicella and 60 patients with Bordetella pertussis (BP), measles virus (MEV) and enterovirus (EV) were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…VZV infection is known to alter miRNA expression in the serum of herpes zoster patients [33,34]. We used small RNA-sequencing to detect miRNAs without the need for annotation and extended quantification over a wider dynamic range.…”
Section: Discussionmentioning
confidence: 99%
“…VZV infection is known to alter miRNA expression in the serum of herpes zoster patients [33,34]. We used small RNA-sequencing to detect miRNAs without the need for annotation and extended quantification over a wider dynamic range.…”
Section: Discussionmentioning
confidence: 99%
“…The Database for Annotation, Visualization and Integrated Discovery (DAVID; Version 6.8) platform was used to analyze the functions of the identified target genes and the diverse signaling pathways in which they participate [16]. …”
Section: Methodsmentioning
confidence: 99%
“…VZV encodes several miRNAs or small non-coding RNAs that regulate VZV infection in host cells [379]. Studies, using quantitative RT-PCR, have shown several circulating miRNAs in patients with VZV infection including: miR-197; miR-629; miR-363; miR-132; miR-122 as well as miR-1906; miR-571; miR1276; miR-1303; miR-943; and miR-661 [378,381]. Hence, circulating miRNAs can be potentially used as biomarkers of active or latent VZV infection [378,381].…”
Section: Sumo Proteins and Sumoylationmentioning
confidence: 99%
“…Studies, using quantitative RT-PCR, have shown several circulating miRNAs in patients with VZV infection including: miR-197; miR-629; miR-363; miR-132; miR-122 as well as miR-1906; miR-571; miR1276; miR-1303; miR-943; and miR-661 [378,381]. Hence, circulating miRNAs can be potentially used as biomarkers of active or latent VZV infection [378,381]. RNA sequencing analysis has shown that VZV infection has profound effect on differentiating keratinocytes thus promoting blistering and desquamation of the skin through upregulation of kallikreins and serine proteases and alteration of epidermal gene expression [382].…”
Section: Sumo Proteins and Sumoylationmentioning
confidence: 99%